Efficiently Regulating the Electrical Properties of Flexible Fabric‐Based Cu3(BTC)2 Thin Film by Introducing Various Guest Molecules. Issue 3 (16th December 2021) - Sun, Chongcai; Wang, Weike; Mu, Xueyang; Zhang, Yifan; Ma, Chuang; Zhu, Jiankang; Wang, Chengbing
Abstract: Recently, the flexibility of 2D conductive metal–organic frameworks (MOFs) is an important precondition for manufacturing high‐performance smart electronic devices. Preparation of MOFs thin film has drawn much attention, and increasingly more MOF thin films have been deposited on different rigid substrates like glass, silicon, and metal electrodes. However, they do not meet the requirements for flexible materials, such as wearable electronic devices. Here, the fabric‐based composites (the integration of MOFs and fabric materials) can solve this problem. Insulating polyester fabric is chosen as a flexible substrate and atom layer deposition (ALD) and the layer‐by‐layer (LBL) method (also called the liquid phase epitaxy method) are combined to synthesize Cu3 (BTC)2 thin film. 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ) and polypyrrole (PPy) are chosen to improve the conductivity of the MOF thin films. The conductivity of Cu3 (BTC)2 thin film is improved by more than four orders of magnitude compared to that of the original sample. This research shows that the large‐area lightweight fabric‐based Cu3 (BTC)2 thin films, which possess excellent uniformity and flexibility and controllable thickness, can be prepared at room temperature; this allows MOFs to be applied in more areas, such as large‐area electronic devices and smart wearable sensing equipment. Abstract : Flexible metal–organic framework thin films named guest@Cu3 BTC2 (Guest = TCNQ/PPy) are successfully deposited on polyester fiber by layer‐by‐layer (LBL) liquid phase epitaxy method. Thin film thickness can be well adjusted via controlling LBL cycle number. The guest molecules significantly enhance the conductivity by more than four orders of magnitude, which remains well after 1000 times bending tests.